Corporate Governance and Financial Performance of Selected Commercial Banks in Kenya - Christine, Pale N.; Mathenge, Joseph Theuri (Journal of Finance and Accounting, 2023)
The primary purpose of this study was to determine whether or not corporate responsibility had an impact on the bottom lines of a sample of Kenyan commercial banks. The research's specific goal was to ascertain how compensation for boards was calculated, consumer protection, nonperforming loans, and risk management on the financial performance of selected Kenyan commercial banks. This research was based on the following theories: agency theory, resource dependency theory, control theory, public choice theory and bank risk management theory. The present investigation employed an expressive research strategy. The 44 Kenyan business banks that were the focus of this analysis as at December 2022. The target respondents were the chief finance officers and credit officers. This study used a census-style methodology because the quantity of participating banks was manageable. Surveys that were semi-structured with a mix of open-ended and closed-ended questions were used to gather primary data. Descriptive statistics like frequency, average, and deviation from the mean, and inductive statistics like regression and correlation analyses were used to examine the data. After that, we use tables and figures to display the results. While respondents generally accept that board remuneration and consumer protection measures have a good impact, the statistical significance differs. NPLs are found to have a negative impact on financial performance, which is consistent with current research advocating responsible lending practices. Risk management is also seen as important; however, opinions differ. The findings of the study emphasize the significance of risk management and the good impact of board compensation and consumer protection, as well as the negative impact of NPLs. Transparent board compensation schemes, strong consumer protection measures, careful NPL management, and thorough risk management methods are among the recommendations. The study recommends future research areas to further the study on the impact of corporate supremacy in financial success. Keywords: Corporate governance Board compensation, Consumer protection, Nonperforming loans, Risk management, financial performance